Development of Practicum Modules Based on CTL (Contextual Teaching And Learning) on Biodiversity Materials for Class X IPA MA NW Pringga Jurang Utara East Lombok - Nening Listari; Rahmatul Izzah (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2022)
This study aims to develop a biology module based on CTL (contextual teaching and learning) for class X IPA MA NW Pringga Jurang Utara students. This development research refers to the ADDIE development model which is carried out through five stages, namely analysis, design, development, implementation, and evaluation. Product development results are validated and assessed by 1 material expert, and 1 media expert. Limited trials in this study were given to 12 students of class X IPA MA NW Pringga Jurang Utara. The instrument in this study was a checklist questionnaire. Data analysis was performed by scoring using a Likert scale, then calculating the average for each aspect. The results of the material expert's assessment were 78% and the results of the media expert's assessment were 97%. While the results of the student response questionnaire were in the very feasible category, namely 87%. Thus this module is suitable for use as teaching material in the biology learning process.